FINANCIAL SUSTAINABILITY OF A FIRM: DEBT-BASED OR EQUITY-BASED FINANCING TO PURSUE? - Sha'ari, Umul Ain'syah; Hamzah, Siti Raihana Bt; Kamil, Karmila Hanim (Journal of Islamic Monetary Economics and Finance, 2023)
This study examines the potential of utilizing equity-based financing by companies in achieving financial sustainability as compared to debt-based financing. To this end, a conceptual framework of equity-based financing over debt-based financing is developed to provide an understanding of the concept of equity-based financing. Subsequently, this study analyses the credit risk exposure between equity and debt for selected sectors in Malaysia. More specifically, a Monte Carlo method is employed to examine the feasibility of the equity-based financing model in fostering the financial sustainability of companies through simulation of equity-based and debt-based financing models from the global financial crisis (GFC) period to the Covid-19 phase. This study finds that equity-based financing can reduce credit risk exposure when returns are tied to the company’s performance. The findings also show that equity-based financing can achieve financial sustainability regardless of any economic events. To conclude, equity-based financing can thus be a viable capital financing option for companies because it can contribute to long-term financial sustainability. Acknowledgment The authors would like to thank the Department of Higher Education, Ministry of Education Malaysia, for the funding that made this study possible.